An experiential-realist Approach to Theology? An Interview with Prof. Klaus Nürnberger - Lange, Hans-Christoph Thapelo (Stellenbosch Theological Journal, 2022)
This interview engages with Prof Klaus Nürnberger on his experiential-realist approach to Theology. Following biographical engagement with Nürnberger in order to contextualise his work, the background to the experiential-realist approach is clarified. Furthermore, the significance of the application of the theory of emergence in this approach is outlined, as well as its consequence for Theology in general, but also Nürnberger's theological Anthropology and Ecclesiology. Moreover, Nürnberger's direction for the future of Theology as a discipline is outlined against the background of the challenges of the modern world.